2020
DOI: 10.1136/bmjopen-2020-037834
|View full text |Cite
|
Sign up to set email alerts
|

Injury patterns in a large-scale ski resort in the host city of 2022 Winter Olympic Games: a retrospective cross-sectional study

Abstract: ObjectivesThe aims of the study are to describe the injury patterns among recreational skiers and snowboarders in China and to provide primary data to guide the reconstruction of regional healthcare facilities to deal with the increasing number of participants in snow sports.DesignRetrospective cross-sectional study.MethodsA retrospective study was performed in Wanlong Ski Resort in Chongli, China. Data of all injured skiers and snowboarders treated in the resort clinic during the 2018–2019 season were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In order to better carry out the corresponding research Cheng [ 20 ], this article combines the chaos theory model with the bee colony algorithm and comprehensively judges the experience design results through bionic algorithm. In the research process, corresponding constraints are added to the threshold and weight settings of the bee colony algorithm to ensure the accuracy of the calculation results [ 21 ]. In addition, by preprocessing the previous data and eliminating irrelevant data content, the speed of calculation can be improved.…”
Section: Discussionmentioning
confidence: 99%
“…In order to better carry out the corresponding research Cheng [ 20 ], this article combines the chaos theory model with the bee colony algorithm and comprehensively judges the experience design results through bionic algorithm. In the research process, corresponding constraints are added to the threshold and weight settings of the bee colony algorithm to ensure the accuracy of the calculation results [ 21 ]. In addition, by preprocessing the previous data and eliminating irrelevant data content, the speed of calculation can be improved.…”
Section: Discussionmentioning
confidence: 99%
“…14 In another study, the rate of upper extremity injuries was found to be higher at 54.3%. 20 In the current study, upper extremity injuries were more common than lower extremity injuries among the patients with skiing experience. At the same time, upper extremity injuries were detected more frequently in the group that did not use protective equipment.…”
Section: Discussionmentioning
confidence: 62%
“…There is a dramatic increase in the number of winter sports enthusiasts in the outdoor ice-snow tourism venues and winter sports venues in various regions, accompanied by significant increase in related sports injuries. 1 According to a large number of reports, the head, neck and knee joints are the most vulnerable parts in winter sports, the most serious of which is traumatic spinal cord injury. 2 Traumatic spinal cord injury, occurring possibly in the cervical, thoracic, lumbar other spinal cord segments, refers to a damage to the structure and function of the spinal cord caused by direct or indirect external forces.…”
Section: Introductionmentioning
confidence: 99%